Efektivitas Flipped Learning Berbasis TIK dalam Meningkatkan High Order Thinking Skills Mahasiswa - Lestari, Wahyu; Aristanti, Wida; Syalwa, Nayoebi Layla; Putri, Elisya Ananda (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the effect of implementing ICT-based flipped learning on the improvement of students’ Higher Order Thinking Skills (HOTS). The research employed a quasi-experimental design with two groups: an experimental group that received ICT-based flipped learning treatment and a control group that participated in traditional learning. The research instruments included a HOTS test (pretest and posttest), a student perception questionnaire, and an observation sheet of learning activities. The findings revealed that the average HOTS score of the experimental group increased from 62.40 to 88.72, with a gain score of 70%, while the control group’s score increased from 61.90 to 75.72 with a gain score of 36.24%. An independent t-test indicated a significant difference between the two groups (p < 0.05), with a large effect size (Cohen’s d = 1.85), demonstrating that ICT-based flipped learning effectively enhances students’ higher-order thinking skills. Furthermore, the questionnaire results showed a highly positive student perception with an average score of 85.14% (categorized as excellent), where 89% of students reported being more active and independent, and 87% stated that they found it easier to understand the material through videos and the LMS. Observational data also indicated high learning participation, with an average score of 4.30 out of 5, reflecting improved activeness, collaboration, and learning readiness. Overall, ICT-based flipped learning was proven effective not only in improving cognitive learning outcomes (HOTS) but also in fostering students’ activeness, independence, and collaboration—key competencies of 21st-century learning.